2010
DOI: 10.1111/j.1751-2980.2010.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal problems in inhalational ketamine abusers

Abstract: Ketamine abusers frequently presented with upper GI symptoms, the commonest of which is epigastric pain (73% of abusers). Abstinence from ketamine abuse can lead to the relief of symptoms, which is an important message for ketamine abusers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 2 publications
2
33
0
Order By: Relevance
“…However, the mechanism of this pathology remains unknown. In a retrospective study of 37 ketamine abusers for the upper gastrointestinal problems [11], 75.7 % of them had upper GI symptoms, which are comparable to our chronic cohort. Fifteen (40.5 %) and 9 (24.3 %) of them had elevated alanine aminotransferase (ALT) and alkaline phosphate (ALP), respectively, but the study was unable to demonstrate any association between epigastric pain and deranged ALT or ALP.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the mechanism of this pathology remains unknown. In a retrospective study of 37 ketamine abusers for the upper gastrointestinal problems [11], 75.7 % of them had upper GI symptoms, which are comparable to our chronic cohort. Fifteen (40.5 %) and 9 (24.3 %) of them had elevated alanine aminotransferase (ALT) and alkaline phosphate (ALP), respectively, but the study was unable to demonstrate any association between epigastric pain and deranged ALT or ALP.…”
Section: Discussionsupporting
confidence: 80%
“…It was shown that the odd ratio of symptomatic relief of the abdominal pain is 12.5 (95 % CI 1.2-130) for those who stopped ketamine versus those who continued its use [11].…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of upper gastrointestinal symptoms is up to 75% (2,12). Gastritis has been demonstrated in 85% of those who had endoscopy (12). Complete relief of the symptoms is observed in most cases when patients abstain from the drug.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic abdominal pain is a common presenting complaint in ketamine abusers. The reported prevalence of upper gastrointestinal symptoms is up to 75% (2,12). Gastritis has been demonstrated in 85% of those who had endoscopy (12).…”
Section: Discussionmentioning
confidence: 99%
“…Serious lower urinary tracts symptoms (increased urinary frequency, urgency, incontinence, hematuria, and dysuria) [14][15][16], gastritis and liver and kidney dysfunction [16,17] are also common in this population. Psychiatric disorders are often comorbid by ketamine include depression, which is remarkably prevalent among chronic ketamine users [18,19], psychosis [18] and cognitive impairment [20][21][22].…”
mentioning
confidence: 99%